MISKONSEPSI MATEMATIKA PADA MAHASISWA SEMESTER III TA. 2018-2019 PGMI UNISDA LAMONGAN - Shoimah, Retno Nuzilatus (MIDA : Jurnal Pendidikan Dasar Islam, 2020)
Abstract Mathematics concepts in elementary school was basic concepts to understand mathematics concepts in the next grade. Therefore, mathematics misconceptions of elementary school teacher should be avoided. It was because of implication to their students. This study was a qualitative descriptive research. The aim of the study was to investigate mathematics misconceptions of PGMI’s students. Subject of the study was 28 students. Purposive sampling was used in the study. Research instrument was a test. Interview was an additional technique to investigate elementary shool teacher mathematics misconceptions and its reason. The study found that mathematics misconceptions of PGMI’s students mostly found in geometry because of preconceptions. Preconceptions mostly affected by a daily meaning. Therefore, development of PGMI’s students mathematics content mastery is needed.